The influence of understanding of reading graphs and understanding sentence on writing ability - Priyono Priyono (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this research is to understand how much the effect of chart and sentence understanding to writing ability of private junior high school student in East Jakarta. This research used quantitative descriptive method with multiple correlation test. Based data analysis can conclude that; 1. There is significant effect between chart (X1) and sentence understanding (X2) to writing ability (X3). From regression coefficient significant result shows by score Sig = 0,001 and Fhitung = 8,374 while Ftabel = 2,79 so that the score Sig = <0,05 and Fhitung > Ftabel shows that regression is significant and means that there is a positive effect between independent variable X1(chart understanding) and X2 (sentence undertstanding) to dependent variable Y (writing ability).